livehappy : Ten Practices for Choosing Joy - Heisz, Deborah K. (New York : HarperElixir, 2016)
An eye-opening shift of perspective on the secret of authentic happiness: how surprisingly simple, everyday acts lead to lifelong joy and fulfillment, from the experts at Live Happy magazine. We are all increasingly hungry for soul-deep happiness. All over the globe, from the hallways of Harvard, where the university s most popular course is a class on positive psychology, to the United Nations resolution naming March 20th the International Day of Happiness, the question of how to be authentically happy concerns millions of lives today. But what if the secret of lasting happiness is actually . . . simple? Now, in Live Happy, the editors of Live Happy magazine, the first lifestyle publication dedicated to the timeless quest to achieve authentic happiness, reveal that true happiness is all about the big impact of small acts of everyday happiness. Organized around the key components of a happy life, from gratitude to attitude and play to purpose, Live Happy brings together illuminating real-life happiness stories, eye-opening examinations on the science of happiness, and simple and inspiring everyday happy acts to empower readers to achieve big happiness breakthroughs. Authentic happiness is within reach and Live Happy shows readers how they can manifest it not only in their own lives but also make a positive and lasting difference in the world.
Includes bibliographical references.
Keywords: Happiness; Conduct of life